Effects of Flavonoid Supplementation on Nanomaterial-Induced Toxicity: A Meta-Analysis of Preclinical Animal Studies - Xie, Dongli; Hu, Jianchen; Wu, Tong; Xu, Wei; Meng, Qingyang; Cao, Kangli; Luo, Xiaogang (Frontiers in Nutrition, 2022)
Background: Nanomaterials, widely applied in various fields, are reported to have toxic effects on human beings; thus, preventive or therapeutic measures are urgently needed. Given the anti-inflammatory and anti-oxidant activities, supplementation with flavonoids that are abundant in the human diet has been suggested as a potential strategy to protect against nanomaterial-induced toxicities. However, the beneficial effects of flavonoids remain inconclusive. In the present study, we performed a meta-analysis to comprehensively explore the roles and mechanisms of flavonoids for animals intoxicated with nanomaterials. Methods: A systematic literature search in PubMed, EMBASE and Cochrane Library databases was performed up to April 2022. STATA 15.0 software was used for meta-analyses. Results: A total of 26 studies were identified. The results showed that ﬂavonoid supplementation could significantly increase the levels of anti-oxidative enzymes (SOD, CAT, GSH, GPx, GST), reduce the production of oxidative agents (MDA) and pro-inflammatory mediators (TNF-α, IL-6, IL-1β, CRP, IgG, NO, VEGF and MPO), alleviate cell apoptosis (manifested by decreases in the mRNA expression levels of pro-apoptotic factor caspase 3, FAS, Bax and increases in the mRNA expression levels of Bcl2), DNA damage (reductions in tail length and tail DNA %) and nanomaterial-induced injuries of the liver (reduced ALT and AST activities), kidney (reduced urea, blood urea nitrogen, creatinine and uric acid concentration), testis (increased testosterone, sperm motility, 17β-HSD as well as reduced sperm abnormalities) and brain (enhanced AChE activities). Most of the results were not changed by subgroup analyses. Conclusion: Our findings suggest that appropriate supplementation of flavonoids may be effective to prevent occupational detriments resulted from nanomaterial exposure.